2003
DOI: 10.1161/01.cir.0000066914.95878.6d
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Wall Shear Stress Inhibits Neointimal Hyperplasia After Stent Implantation

Abstract: Background-Low wall shear stress (WSS) increases neointimal hyperplasia (NH) in vein grafts and stents. We studied the causal relationship between WSS and NH formation in stents by locally increasing WSS with a flow divider (Anti-Restenotic Diffuser, Endoart SA) placed in the center of the stent. Methods and Results-In 9 rabbits fed a high-cholesterol diet for 2 months to induce endothelial dysfunction, 18 stents were implanted in the right and left external iliac arteries (1 stent per vessel). Lumen diameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 20 publications
1
63
0
1
Order By: Relevance
“…Following coronary stent deployment, sites of aggressive neointimal hyperplasia also correspond to sites subjected to non-physiological flow conditions, and this has been attributed to increased endothelial dysfunction and permeability. 6,17,18,20,21,52,71,79,88 The hemodynamic impact of the investigated stents was evaluated in terms of the relative residence time distribution predicted upon the lumen surface during the third cardiac cycle. The RRT accounts for temporal variations in both the magnitude and the orientation of the instantaneous wall shear stress vector and is calculated as follows:…”
Section: Analysis Of Balloon-expandable Coronary Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following coronary stent deployment, sites of aggressive neointimal hyperplasia also correspond to sites subjected to non-physiological flow conditions, and this has been attributed to increased endothelial dysfunction and permeability. 6,17,18,20,21,52,71,79,88 The hemodynamic impact of the investigated stents was evaluated in terms of the relative residence time distribution predicted upon the lumen surface during the third cardiac cycle. The RRT accounts for temporal variations in both the magnitude and the orientation of the instantaneous wall shear stress vector and is calculated as follows:…”
Section: Analysis Of Balloon-expandable Coronary Stentsmentioning
confidence: 99%
“…6,17,18,20,21,52,71,79,88 In light of these observations, a significant body of research has been carried out in this area. Due to the difficulty involved in the evaluation of these phenomena in an in vivo setting however, a large portion of this research has been carried out using computational methods of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Increases in arterial wall shear stress prevent vascular remodeling leading to thickening of the vascular wall and inflammation, 2 whereas decreases in arterial wall shear stress promote arterial remodeling and inflammation. 2,3 Additionally, low wall shear stress leads to degradation of the internal elastic lamina (IEL). 5 Despite these findings, the underlying mechanisms by which shear regulates proteases degrading vessel wall matrix and IEL are not well described.…”
mentioning
confidence: 99%
“…Thus, a low shear stress could lead to reduction of the cross-sectional area of renal ostium owing to presence of stent wires (because of formation of neointimal hyperplasia on the stent surface). It has been reported that augmentation of wall shear stress is accompanied by a local reduction in neointimal hyperplasia [21]. Another potential risk of a low shear stress is the formation of artery plaque or atherosclerosis in the aortic branches [22].…”
Section: Discussionmentioning
confidence: 99%